Autoimmune manifestations associated with lymphoma: characteristics and outcome in a multicenter retrospective cohort study. Issue 6 (3rd June 2018) - Jachiet, Vincent; Mekinian, Arsène; Carrat, Fabrice; Grignano, Eric; Retbi, Aurelia; Boffa, Jean-Jacques; Ronco, Pierre; Rondeau, Eric; Sellam, Jérémie; Berenbaum, Francis; Chazouillères, Olivier; Capron, Jean; et al.
Abstract: This French multicenter retrospective cohort study aimed to describe the autoimmune manifestations (AIMs) associated with lymphoma among patients hospitalized between 2005 and 2016 in three French University Hospitals. Among 2503 patients with lymphoma, 108 (4.3%) had AIMs, mostly autoimmune cytopenias (71.3%), neurological diseases (10.2%), kidney diseases (6.5%), systemic vasculitis (5.6%) and others. As compared with the 2395 lymphoma patients without AIMs, those with AIMs were older ( p  = .01), more frequently had B-cell chronic lymphocytic leukemia ( p  < .01) and less frequently diffuse large B-cell lymphomas ( p  = .01) and Hodgkin lymphoma ( p  = .01). The 5-year overall survival with lymphoma was 65% and 79% ( p  = .03) with and without AIMs. This large cohort study shows that various types of AIMs, mostly cytopenias, could be associated with lymphoma and affect the overall outcome with lymphoma, in particular for B-cell non-Hodgkin lymphoma ( p  = .01) and T-cell non-Hodgkin lymphoma ( p  = .01), with no survival difference noted for other types of lymphoma ( p  = .2).